EFEKTIVITAS TERAPI PSIKORELIGIUS TERHADAP PENURUNAN TINGKAT DEPRESI LANSIA DI PANTI SOSIAL TRESNA WERDHA ABIYOSO SLEMAN YOGYAKARTA - Saseno Saseno; Siti Arifah; Rusdi Rusdi (Poltekkes Kemenkes Semarang, 2013)
Based on an implemented surrvey at panti sosial tresna werdha abiyoso, it was found that with depression used geriatric depression scale from 80 person as respondent there are 24 person depression. One of the ways to decrease of the depression by psychoreligius therapy. This study is a quasi experiment with non equivalent control group design. This research aimed to examine the effectiveness of psychoreligius teraphy in decreasing depression in elderly. The subject of this study were 34 elderlys whom stayed at panti sosial tresna werdha abiyoso. They were selected and divided into two groups. First group had 17 people that considered as experiment group and secondly group had 17 people that considered as control group. Intrument being used was the geriatric depression scale (GDS). The analysis being used to test the diffrence of treatment and control group scores is SPSS one way student significance level of p =0,05. The result of this study showed that the pretest being done, there was no diffrence between mean score of depression experimental group and control group. However, when the posttest being done there was significant difference between two groups. After given psychoreligius therapy, the depression scale in elderlys of the experimental group was lower than control group. Therefore, it be concluded that psychoreligius therapy is effective in decreasing the depression in elderlys at panti sosial tresna werdha abiyoso.